Control interno de los procesos financieros en la empresa pública de saneamiento ambiental EMSABA EP, de la ciudad de Babahoyo - Navarrete Vargas, Kleber Mauricio (2021)
Emsaba, is a Municipal Public Environmental Sanitation Company of the Babahoyo canton of the Los Ríos Province, whose objective is the attention, study, management and solution in all phases and processes of citizen needs in the provision and supply of services drinking water, sewerage, among others. At present, internal control plays a fundamental role in the management of the administrative and financial processes of public entities, where its purpose is to provide security and transparency to the information, as well as to ensure that the results obtained demonstrate compliance with the objectives. raised. The objective of this case study is to identify the existing shortcomings in Emsaba regarding the internal control of financial processes and thus determine the effects that these entails. He focused on "Auditing and Control", as a sub-line of investigation of the Accounting and auditing career. Finally, the research was developed, using the descriptive and exploratory method, where bibliographic and scientific information could be collected, which were included in the research development.